Exoantigen test for Cladosporium bantianum, Fonsecaea pedrosoi, and Phialophora verrucosa. - Espinel-Ingroff, A (1986)
Exoantigens from 10-day-old cultures of 100 isolates of pathogenic and saprophytic dematiaceous fungi were analyzed by the exoantigen test. Antisera to Cladosporium bantianum ATCC 10958, Fonsecaea pedrosoi CDC AMO-B06, and Phialophora verrucosa CDC AMO-C12 were prepared in New Zealand rabbits immunized with soluble antigens from 1-month-old cultures. Absorbed and nonabsorbed antisera and exoantigens from the same organisms were used as reference reagents. Serologic reactions were analyzed in terms of the presence or absence of lines of identity or nonidentity. These reactions allowed presumptive differentiation of C. bantianum, F. pedrosoi, and Phialophora verrucosa from other dematiaceous fungi, including Cladosporium spp. (28 isolates), Exophiala spp. (18 isolates), Fonsecaea spp. (17 isolates). Lecythophora hoffmannii (4 isolates), Phaeoannellomyces werneckii (3 isolates), Phialophora spp. (17 isolates), Wangiella dermatitidis (9 isolates), and Rhinocladiella spp. (4 isolates).